Grey System Theory Supported Markowitz Portfolio Optimization during High Volatility Periods - (:unkn) unknown (RESEARCH INFORMATION LTD, 2016)
Investment in stocks in high volatility periods is more difficult for investors relative to periods with lower volatility. In these high volatility periods, the efficiency levels of markets tend to decrease and the probability investors facing asymmetric information increase. As such, certain modern approaches are needed for not only stock selection, but also for portfolio creating with selected stocks. This study runs a Markowitz Portfolio Optimization supported by Grey Systems Theory on selected stocks from the BIST 30 Index for a time period during the 2008 Global Financial Crisis. The purpose of this study is to develop a model, which can be used for investor decision making in the periods of uncertainty. Additionally, this study also compares the performances of the developed model, Hybrid portfolios and Traditional portfolios. The results of the study show that the developed models with a modern approach can be applicable and successful for periods with high volatility.
Keywords: Decision Analysis; Portfolio Optimization; Financial Forecasting; Grey System Theory; GM(1,1) Model; ELECTRICITY DEMAND; MODEL; SELECTION; PREDICTION; PERFORMANCE; CONSTRAINTS